The Legislative Drafting Principles of the Legal Model for Corruption Crimes in Libyan Law (Issues and Proposed Solutions) (Journal of Human Sciences, 2025)
Legislative drafting is both a science and an art that enables the legislator to achieve the intended objectives of legislation and to improve the legal system by alleviating the instability caused by frequent legislative amendments. This is accomplished through a set of standards and guidelines that shape legal provisions in alignment with the state's legislative policy. However, the Libyan legislator's approach to corruption crimes as stipulated in Article (3/7) of Law No. (11) of 2014 and its amendment by Law No. (5) of 2024 deviates from proper legislative drafting principles. This deviation is evident in the lack of a clear definition of corruption crimes, non-compliance with classification standards, and deficiencies in criminal penalties—particularly regarding fixed and relative quantitative gradation, as well as the rules of exemption or mitigation of punishment. Moreover, the legislation is limited to mere referrals to other laws without providing adequate legal structure.